2017
DOI: 10.3389/fmicb.2017.00463
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Cultures Contain Cell Size and Density Specific Sub-populations of Cells with Significant Differential Susceptibility to Antibiotics, Oxidative and Nitrite Stress

Abstract: The present study shows the existence of two specific sub-populations of Mycobacterium smegmatis and Mycobacterium tuberculosis cells differing in size and density, in the mid-log phase (MLP) cultures, with significant differential susceptibility to antibiotic, oxidative, and nitrite stress. One of these sub-populations (~10% of the total population), contained short-sized cells (SCs) generated through highly-deviated asymmetric cell division (ACD) of normal/long-sized mother cells and symmetric cell divisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(93 citation statements)
references
References 79 publications
3
89
0
Order By: Relevance
“…In some studies mycobacterial cell length and elongation rates are associated with differential susceptibility to host- and antibiotic-induced stress ( Aldridge et al, 2012 ; Richardson et al, 2016 ; Vijay et al, 2017 ). The exact mechanisms contributing to such stress tolerance is not clear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some studies mycobacterial cell length and elongation rates are associated with differential susceptibility to host- and antibiotic-induced stress ( Aldridge et al, 2012 ; Richardson et al, 2016 ; Vijay et al, 2017 ). The exact mechanisms contributing to such stress tolerance is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…In M. smegmatis sub-populations of cells were observed to grow, divide, and die during the persistence phase of isoniazid killing, and this was independent of single-cell growth rates ( Wakamoto et al, 2013 ). It is also observed that cell size- and density-specific subpopulations exist in mycobacteria, and long cell size is associated with tolerance to host and antibiotic stress conditions ( Vijay et al, 2017 ). Antibiotic tolerant cells can also give rise to antibiotic-resistant cells in M. tuberculosis during antibiotic treatment, possibly due to growth under antibiotic selection pressure ( Wakamoto et al, 2013 ; Sebastian et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanism underneath this phenomenon has been described, with LamA (formerly Mmps3), a member of the divisome, inhibiting growth at nascent new poles ( Rego et al, 2017 ). Several evidences indicated that Mycobacterium smegmatis cells of different size, generated by asymmetric division, had different sensitivity to drugs: accelerator cells were shown to be more susceptible than alternators to drugs targeting the cell wall biosynthesis such as cycloserin, meropenem, and INH, however, they were less susceptible to rifampicin ( Aldridge et al, 2012 ; Richardson et al, 2016 ; Vijay et al, 2017a ), suggesting that asymmetric cell division can contribute to the formation bacterial subpopulations more tolerant to drugs. Interestingly, deletion of lamA in M. tuberculosis leads to the loss of single-cell heterogeneity and faster killing by vancomycin and rifampicin ( Rego et al, 2017 ).…”
Section: Cellular Heterogeneity By Asymmetric Division: a Way To Devementioning
confidence: 99%
“…One serious challenge in the treatment of TB caused by both susceptible and resistant Mtb strains is the high population heterogeneity of mycobacterial cells (30)(31)(32)(33)(34)(35)(36)(37)(38). Asymmetric growth (mycobacteria elongate preferentially from the old pole) and asymmetric septum placement give rise to daughter cells of unequal sizes and growth rates and, as indicated by some reports, different susceptibilities to antibiotics (30,39,40). Moreover, exposure to stress further diversifies the population (41,42), suggesting that mycobacteria utilize heterogeneity as key survival strategy under stressful conditions.…”
Section: Introductionmentioning
confidence: 99%